A Novel Multimodal Transport Model for School Commuting - Deng, Haoran; liu, Huasheng; Li, Jin; Zhao, Yuqi; Yang, Sha; Dong, Kui (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
During peak hours, the roads surrounding schools often become a source of concern due to severe traffic congestion. This not only leads to a substantial increase in travel time but also poses heightened safety risks. This study proposes a multimodal transport model that integrates private cars, shared parking spaces, and school buses (CPB) to address these challenges. The model aims to improve traffic efficiency and reduce safety hazards. The approach involves two key phases: identifying optimal locations for private car parking and optimizing school bus routes. Results show an 18.53% reduction in private car costs and an 8.13% decrease in traffic delays within the road network. The advantages of this model become particularly significant when student commuting demand exceeds 70% of peak transportation demand. This study provides a robust scientific foundation for developing traffic management strategies around schools.